Vegetation Diversity Supporting the Activities of Cenderawasih Birds (Paradisaeidae) in the Tablasupa Village Forest, Depapre District, Papua - Katrina Sada; Alfred Alfonso Antoh; Edoward Krisson Raunsay (Jurnal Penelitian Pendidikan IPA, 2026)
This limited knowledge has the potential to hamper community-based conservation efforts, as effective habitat protection requires a detailed understanding of the vegetation types that support the entire life cycle of the animal. Therefore, focused research is needed to map the types of vegetation or trees that primarily support the activities of the Cenderawasih birds in the Tablasupa Village forest. This research method uses quantitative and qualitative descriptive methods using exploratory survey techniques. Study aims to describe the habitat of the Cenderawasih bird (family Paradisaeidae) in the forest of Tablasupa Village, Depapre District, Jayapura Regency, Papua. Identifying the tree species used by the bird in carrying out its activities. The Cenderawasih bird is an endemic animal of Papua that has high ecological, aesthetic, and cultural value. Data collection was carried out at predetermined observation spots at the research location, with the methods used including direct observation, exploration, and literature study. The data obtained were analyzed using qualitative descriptive analysis. This study shows that there are certain trees that can be used by the Cenderawasih bird to carry out its activities. Eleven tree species are used by the Cenderawasih bird for various activities, namely seven tree species as play areas, three species as food trees, and one tree species as a bed for the Cenderawasih bird. The presence of certain tree species greatly influences the survival and activities of the Cenderawasih bird.